Відсутність суспільної небезпеки як конститутивна ознака обставин, що виключають злочинність діяння - Кваша, О.; Михальченко, Н.; Kvasha, O.; Mikhalchenko, N. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті наведено аргументи щодо комплексного (міждисциплінарного) характеру інституту обставин, що виключають злочинність діяння. Цей інститут включає обставини, передбачені не лише КК, а й іншими нормативно-правовими актами. Існують реальні перспективи законодавчого закріплення таких обставин в КК України, зокрема й згоди потерпілого. У результаті проведеного дослідження запропоновано зміни до розділу VIII Загальної частини КК України, а саме – наповнення новим змістом статті 36 КК України щодо надання суду права визнавати такими, що виключають злочинність діяння, й інші обставини, які наразі не зазначені у цьому розділі. The authors convincingly argue that public danger is the internal nature of the crime as it is a phenomenon of the objective reality and the principal item of the legal definition of the concept of crime. Accordingly, the absence of such a feature a priori means the absence of a crime. The article contains arguments concerning complex (interdisciplinary) nature of the institute of circumstances that exclude the criminality of a doing. This institute embraces the circumstances envisaged not only by the Criminal Code (Criminal Code of Ukraine), but also by other normative-legal acts. There are real prospects for legislative consolidation of such circumstances in the Criminal Code of Ukraine, especially when it concerns the concept of consent of the victim. The key findings of the study provide grounds to suggest modifications to the Section VIII of the General Part of the Criminal Code of Ukraine, namely Article 36 entitled «Legal grounds for the exclusion of criminal offenses and criminal liability». In author’s opinion it should be worded as follows: «1.A person who committed a conscious volitional act like a crime on objective grounds, but it is socially acceptable and is not prohibited by law of Ukraine shall not be a subject to criminal liability. 2. The court may recognize the circumstances as such that exclude criminality, but are not provided for in this Code, outwardly similar to the criminal act containing no public danger».
Absence of Public Danger as a Defining Feature of the Circumstances that Exclude the Criminality of the Doing
Keywords: обставини, що виключають злочинність діяння; згода потерпілого; суспільна небезпека; суспільна корисність; злочин; circumstances excluding the crime of an act; consent of the victim; public/social danger; public utility; crime